Crises and Capital Requirements in Banking - Morrison, Alan D; White, Lucy (American Economic Review, 2005)
We analyze a general equilibrium model in which there is both adverse selection of, and moral hazard by, banks. The regulator can screen banks prior to giving them a licence, audit them ex post to learn the success probability of their projects, and impose capital adequacy requirements. Capital requirements combat moral hazard when the regulator has a strong screening reputation, and they otherwise substitute for screening ability. Crises of confidence can occur only in the latter case, and contrary to conventional wisdom, the appropriate policy response may be to tighten capital requirements to improve the quality of surviving banks.